PRE- AND POSTNATAL EXPOSURE TO KYNURENINE CAUSES COGNITIVE DEFICITS IN ADULTHOOD - Pocivavsek, Ana (2012)
Levels of kynurenic acid (KYNA), an endogenous product of tryptophan degradation, are elevated in the brain and cerebrospinal fluid of individuals with schizophrenia (SZ). This increase has been implicated in the cognitive dysfunctions seen in the disease since KYNA is an antagonist of the α7 nicotinic acetylcholine receptor and the NMDA receptor, both of which are critically involved in cognitive processes and in a defining neurodevelopmental period in the pathophysiology of SZ. We tested the hypothesis that early developmental increases in brain KYNA synthesis might cause biochemical and functional impairments in adulthood. To this end, we stimulated KYNA formation by adding the KYNA precursor kynurenine (100 mg/day) to the chow fed to rat dams from gestational day 15 to postnatal day 21 (PD 21). This treatment raised brain KYNA levels in the offspring by 341% on PD 2 and 210% on PD 21. Rats were then fed normal chow until adulthood (PD 56-PD 80). In the adult animals, basal levels of extracellular KYNA, measured in the hippocampus by in vivo microdialysis, were elevated (+12%), whereas extracellular glutamate levels were significantly reduced (−13%). In separate adult animals, early kynurenine treatment was shown to impair performance in two behavioral tasks linked to hippocampal function, the passive avoidance test and the Morris water maze test. Collectively, these studies introduce a novel, naturalistic rat model of SZ and also suggest that increases in brain KYNA during a vulnerable period in brain development may play a significant role in the pathophysiology of the disease.